Plants to Remotely Detect Human Decomposition?. (October 2020) - Brabazon, Holly; DeBruyn, Jennifer M.; Lenaghan, Scott C.; Li, Fei; Mundorff, Amy Z.; Steadman, Dawnie W.; Stewart, C. Neal
Abstract : In the USA, 100 000 people go missing every year. Difficulty in the rapid identification of sites of human decomposition complicates the recovery of bodies, especially in forests. We propose that spectral responses in tree and shrub canopies could act as guides to find cadavers using remote sensing platforms for societal benefit.